A caminho do lar: a narrativa dos anúncios de eletrodomésticos - Santos, Edgar Souza (2009)
In the first decades of the twentieth century capitalist society underwent a profound process of transformation. The advances in the field of science and technology have substantially changed the production relations, and imposed on the West and later the world, the logic of a consumer society. This change was due to the emergence and assertion of power as the main fuel of the new company. Two factors were responsible for this transformation: the need for viable investments in the electricity sector, which was only possible with the production and introduction of appliances within the homes, as well as running these ads in technical objects present in entertainment magazines. The years 1940 and 1950 represented a timely moment in the process of building a society based on consumption, which led to the transformation of social areas in particular, the spaces of the home. The insertion of appliances in homes printed a radical transformation in everyday practices of the housewife at home, which can be perceived, while the narratives written text and imagery, present in ads polishers, blenders, air circulators, coolers, blenders, radios televisions, among others. By spreading the idea that it was necessary to modernize the home and that would only be possible by acquiring a diverse range of technical devices, ads for household appliances introduced in the sign of speed and modernity. This research has sought to reflect and problematize the process of building the modern idea of home from different narratives represented in ads for household appliances, gifts in entertainment magazines in Brazil, in the years 1940-50